EPIDEMIOLOGY OF URINARY TRACT INFECTION IN THE ARAL SEA REGION - У. А. Худайбергенов; Ш. А. Аббосов (Galaxy International Interdisciplinary Research Journal, 2023)
It is known that the best way to prevent the development of any disease is to eliminate its cause. When drawing up plans for the implementation of therapeutic and preventive measures, as well as the development of medical care, the health care organizer is almost always guided by statistical data on the prevalence of individual groups of diseases. At the same time, as a rule, the dynamics of morbidity, its frequency and prevalence by region and age categories of the population are taken into account.